Phenotype, treatment practice and outcome in the cobalamin‐dependent remethylation disorders and MTHFR deficiency: Data from the E‐HOD registry. Issue 2 (17th February 2019) - Huemer, Martina; Diodato, Daria; Martinelli, Diego; Olivieri, Giorgia; Blom, Henk; Gleich, Florian; Kölker, Stefan; Kožich, Viktor; Morris, Andrew A.; Seifert, Burkhardt; Froese, D. Sean; Baumgartner, Matthias R.; et al.
Abstract : Aim: To explore the clinical presentation, course, treatment and impact of early treatment in patients with remethylation disorders from the European Network and Registry for Homocystinurias and Methylation Defects (E‐HOD) international web‐based registry. Results: This review comprises 238 patients (cobalamin C defect n = 161; methylenetetrahydrofolate reductase deficiency n = 50; cobalamin G defect n = 11; cobalamin E defect n = 10; cobalamin D defect n = 5; and cobalamin J defect n = 1) from 47 centres for whom the E‐HOD registry includes, as a minimum, data on medical history and enrolment visit. The duration of observation was 127 patient years. In 181 clinically diagnosed patients, the median age at presentation was 30 days (range 1 day to 42 years) and the median age at diagnosis was 3.7 months (range 3 days to 56 years). Seventy‐five percent of pre‐clinically diagnosed patients with cobalamin C disease became symptomatic within the first 15 days of life. Total homocysteine (tHcy), amino acids and urinary methylmalonic acid (MMA) were the most frequently assessed disease markers; confirmatory diagnostics were mainly molecular genetic studies. Remethylation disorders are multisystem diseases dominated by neurological and eye disease and failure to thrive. In this cohort, mortality, thromboembolic, psychiatric and renal disease were rarer than reported elsewhere. Early treatment correlates with lower overall morbidity but is less effective in preventing eye disease and cognitive impairment. The wide variation in treatment hampers the evaluation of particular therapeutic modalities. Conclusion: Treatment improves the clinical course of remethylation disorders and reduces morbidity, especially if started early, but neurocognitive and eye symptoms are less responsive. Current treatment is highly variable. This study has the inevitable limitations of a retrospective, registry‐based design.